Ni/Fibrous type SBA-15: Highly active and coke resistant catalyst for CO2 methanation - Syahida Nasuha, Bukhari; Chi, Cheng Chong; Setiabudi, Herma Dina; Yoke, Wang Cheng; Lee, Peng Teh; Aishah, Abdul Jalil (Elsevier, 2021)
The rod-like SBA-15 was transformed into fibrous type SBA-15 (F-SBA-15). The Ni/F-SBA-15 was catalytically evaluated in CO2 methanation and compared with conventional Ni/SBA-15. A superior catalytic performance was shown by Ni/F-SBA-15 (CO2 conversion = 99.7%, and CH4 yield = 98.2%) than Ni/SBA-15 (CO2 conversion = 91.1%, and CH4 yield = 87.5%). This phenomenon was attributed to the favorable physicochemical properties of F-SBA-15 as evidenced by the characterization results. A higher homogeneity of finer Ni was embedded onto the F-SBA-15 support, subsequently strengthened the Ni interaction with F-SBA-15, and increased the amount of moderate basic sites. The in situ FTIR studies evidenced the CO2 methanation over both catalysts proceeded via CO2 dissociation pathway. Three intermediate species (linear carbonyl, unidentate, and bidentate carbonates) were detected for Ni/F-SBA-15, while only bidentate carbonates were detected for Ni/SBA-15, signifying excellent catalytic attributes of Ni/F-SBA-15. Additionally, Ni/F-SBA-15 demonstrated higher stability and coke resistance ability than Ni/SBA-15.